Employees of commercial banks learning to unlearn: a case study on the impact of electronic banking in the commercial banks of Bangladesh - Oeshwik, Ahmed (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2020)
Link to publisher's homepage at https://ijbt.unimap.edu.my